PENGARUH PENGETAHUAN, SIKAP DAN KESEJAHTERAAN KEUANGAN TERHADAP MINAT BERINVESTASI - Irma Oktarina Safitri; Frasto Biyanto; Baldric Siregar; Miswanto, Miswanto (Bajang Institute, 2025)
The purpose of this study was to determine how financial knowledge, financial attitudes, and financial well-being affect investment interest. Using primary data by distributing questionnaires through social media with a purposive sampling method, with 75 samples with the criteria of individuals living in the Special Region of Yogyakarta with the criteria of having a monthly income and being interested in investing. Data were processed using Partial Least Square (PLS) 4 to predict the relationship between variables. The results showed that financial well-being did not affect investment interest, but financial knowledge and attitudes had a significant positive effect on investment interest.